The Montreal protocol: developing countries import of Halons - Mat Ghani, Gairuzazmi (Economics Bulletin, 2007)
Base on the model of legal and illegal trade in CFC from Ivanova (2007), this paper empirically analyzes the affects of the Montreal Protocol on imports of Halons, and hence their consumption, in developing countries. We show that countries with high income level have decreased their import of Halons, but ratifiers of the Protocol import more Halons than non-ratifiers.